Climate security in Central America - Penel, Charlotte; Madurga Lopez, Ignacio M.; Medina, Leonardo (2023)
This report provides an in-depth investigation into climate security risks in the Central American region. It examines the interlinkages between climate change, human security and conflict, looking at how the impacts of climate change can exacerbate security risks for individuals, communities and states. The report first provides a detailed overview of the climate context in the Central American region examining both current climate trends and future projections, underlying the high degree of climate exposure and vulnerability in the region. It also examines past and current fragility, conflict and violence dynamics to outline their detrimental impact on states and communities as well as understand their underlying drivers It also highlights the socioeconomic factors such as poverty, food insecurity and inequality that play a role in exacerbating human security and conflict risks in the region. Through an extensive research process of examining academic and grey literature, taking into account the socioeconomic and political contexts, this report uncovers three climate security pathways through which the interconnections between climate change, human security and conflict can arise.